Iridium‐Catalyzed [4+2] Annulations of β‐Keto Sulfoxonium Ylides and o‐Phenylenediamines: Mild and Facile Synthesis of Quinoxaline Derivatives. Issue 24 (16th June 2020) - Wang, Xiao‐Tong; Song, Jia‐Lin; Zhong, Mei; Kang, Hua‐Jie; Xie, Hui; Che, Tong; Shu, Bing; Peng, Dongming; Zhang, Luyong; Zhang, Shang‐Shi
Abstract : A synthetic method for quinoxaline derivatives from the [4+2] annulation of β‐keto sulfoxonium ylides and o ‐phenylenediamine by using (Cp*IrCl2 )2 catalyst is described. This novel protocol features mild reaction conditions, moderate to excellent yields, wide substrate scope, and high functional‐group compatibility. Moreover, this cyclization strategy was successfully applied in late‐stage modification for structurally complex bioactive compounds. Abstract : The effective Cp*Ir III ‐catalyzed [4+2] tandem cyclization reaction of β‐keto sulfoxonium ylides and o ‐phenylenediamine has been reported for the first time, furnishing monosubstituted quinoxaline and its derivatives with moderate to excellent yield. This novel protocol exhibits broad substrate scope as well as feasibility for late‐stage modification of drug molecules